The effect of buffer strip width on cost efficiency - Tredanari, Antonio (2011)

(untitled)
The objective of this study is to analyze the cost-efficiency of buffer zone schemes in Sweden in the context of European Directives, national agri-environmental support programmes and environmental targets to be achieved. The study includes a comprehensive overview of the scientific literature on the effectiveness of buffer zones in retaining pollutants and a modelling exercise. The exercise evaluates the effect of buffer zone width on reducing phosphorus losses using the model ICECREAM DB and Swedish data. The study then analyzes how the parameters that influence the effectiveness of different widths may impact the cost-effectiveness of policy alternatives. What emerges is that the width of a buffer might not be that influential as other site conditions when looking at the cost-efficiency in reducing the load of phosphorous from agricultural fields. Eventually, a more down-scaled and differentiated payment scheme for buffer zones (of different designs) based on more localized and easy-to-establish parameters (such as climate and soil type, but also the load of P and reduction targets) would produce a more cost-effective approach.